INTEGRATING ISLAMIC VALUES INTO THE DEVELOPMENT OF DAILY ROUTINE UNIT OF THE EIGHTH GRADE STUDENT AT MTS MADANI PAO-PAO - Indah Fadhilah Rahman; Kamsinah; Qani'ah (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
This research aims at integrating Islamic Values into English material especially in basic competencies 3.7 and 4.7 about Daily Routine for the eighth-grade students at MTs Madani Pao-Pao based on the 2013 curriculum. Based on the preliminary study, the researcher found that the textbook that used in the school was too general and still far from the term integrated with Islamic values. The research design used in this study was Research and Development (R&D). The development model used was the ADDIE model. It consists of need analysis, design, development, implementation, and evaluation. The procedures included analyzing materials needed by distributing questionnaires to the students and analyzing the basic competencies used, designing a blueprint of materials, and developing the English materials through the ADDIE model. In this research, the expert was involved to validate the product. There were two systematic aspects that they validated of the product: the aspect of the content/material and the aspect of learning. Therefore, the result indicated that based on experts’ judgment as well as product development result, the developed basic competencies 3.7 and 4.7 about Daily Routine materials was applicable to be taught at the eighth-grade students of Junior High School as topics in English for them.